Testimonial for Christ?: A theology of witness in the face of Testimonial studies - Oorschot, Frederike van (International journal of systematic theology, 2026)
As a contemporary mode of discourse and basic concept of Christian existence, the concept of witnessing, at the interface of public theology and testimonial studies, is examined with regard to its epistemic dimension: What implications does witnessing as knowledge practice have for theology? To this end, the paper outlines the understanding of witness: Witnessing is transcendent across time, but not ahistorical, subjective and related to an object, individual and decodable, true-speaking and not evidence-based, direct and reflexive, convincing and epistemically modest, trusting and not naïve. As witnessing leads to a community that is entrusted with a responsibility, the paper examines the theological questions attached. Finally, a theology of witness is outlined understood as epistemic responsibility in the community of academic theology associated with the call for epistemic clarity on the one hand and an attitude of epistemic modesty and hospitality on the other.